Cashmah-yi Masīḥī - Aḥmad, G̲h̲ulām, 1839?-1908.; Tisdall, William St. Clair, 1859-1928. ([Rabwah] : [publisher not identified], 2004)
In refutation to Yanābīʼ al-Islām, translation of Source of Islam by William St. Clair Tisdall.
"Yah risālah ek ʻĪsāʼī kī kitāb Yanābiʼ al-Islām ke javāb meṉ tālīf ho kar is kā nām mandarjah zel rakhā gayā"--T.p.
Originally published: Qādiyān : Maṭbaʻ Megzīn, 1906.
Mode of access: Internet.
In Urdu.
Keywords: Tisdall, William St. Clair, -- 1859-1928.; Jesus Christ -- Islamic interpretations; Christianity -- Controversial literature